Recovery, Characterization, Functionality and Applications of Bioactive Compounds from Food-Plant Products and Their By-Products - Ariel Fontana (Plants, 2023)
Sustainability in the food industry has been frequently linked to strategies that avoid, or at least minimize, the amount of by-products in food production [...]